Incidence, causes and consequences of moderate and severe traumatic brain injury as determined by Abbreviated Injury Score in the Netherlands - Denise Jochems (Nature Portfolio, 2021)
Abstract Traumatic brain injury (TBI) is a leading cause of death and disability. Epidemiology seems to be changing. TBIs are increasingly caused by falls amongst elderly, whilst we see less polytrauma due to road traffic accidents (RTA). Data on epidemiology is essential to target prevention strategies. A nationwide retrospective cohort study was conducted. The Dutch National Trauma Database was used to identify all patients over 17 years old who were admitted to a hospital with moderate and severe TBI (AIS ≥ 3) in the Netherlands from January 2015 until December 2017. Subgroup analyses were done for the elderly and polytrauma patients. 12,295 patients were included in this study. The incidence of moderate and severe TBI was 30/100.000 person-years, 13% of whom died. Median age was 65 years and falls were the most common trauma mechanism, followed by RTAs. Amongst elderly, RTAs consisted mostly of bicycle accidents. Mortality rates were higher for elderly (18%) and polytrauma patients (24%). In this national database more elderly patients who most often sustained the injury due to a fall or an RTA were seen. Bicycle accidents were very frequent, suggesting prevention could be an important aspect in order to decrease morbidity and mortality.